A menedék : Corrie ten Boom visszaemlékezései : 1892-1945 - Ten Boom, Corrie, 1892-1983.; Sherrill, Elizabeth, 1928-; Sherrill, John L., 1923- (Chappaqua, N. Y. : [s.n.], 1968)
The amazing story of Corrie Ten Boom, a heroine of the Dutch Resistance who helped Jews escape from the Nazis and became one of the most remarkable evangelists of the 20th century, is told in her classic memoir.
Mimeographed copy.
HU OSA 430 - Donation of Zsuzsa Horváth
Keywords: Ravensbrück (Concentration camp).; World War, 1939-1945 -- Concentration camps -- Germany -- Ravensbrück